Rigid Gas Permeable (RGP) as Keratoconus Management After Corneal Collagen Cross-Linking (CXL) Procedure: a Case Report: Poster Presentation - Case Report - Resident - Miranti Laras Ayu Sanusi; Karmelita Satari; Joan Sherlone Hutabarat; Ine Renata Musa; Susanti Natalya Sirait (Majalah Oftalmologi Indonesia, 2023)
Introduction : Rigid Gas Permeable (RGP) contact lenses are the mainstay for keratoconus patients and widely used. This case report presents RGP as a management for keratoconus after Corneal Collagen Cross- Linking (CXL) procedure. Case Illustration : A 22-year-old woman diagnosed with keratoconus since eight months ago, came for vision correction. She had CXL performed on both eyes. Ophthalmologic examination revealed uncorrected visual acuity of 0.63 in the right eye (RE) and 0.08 in the left eye (LE). Her best-corrected visual acuity (BCVA) was 1.0 in the RE with -0.75 D and 0.125 in the LE with -2.00 D. Anterior segment examination of the RE was unremarkable, but the LE has Vogt’s striae and Munson's sign (Figure 1). Corneal topography for the LE showed K1 64.7D/5.2 mm, K2 68.7D/4.9 mm, and Kmean 66.7D/5.1 mm. She was fitted with trial lens of BC 5.40 and the fit was loose. She then fitted with a BC of 5.50 mm showed a good fit result. RGP contact lenses were prescribed with S -8.50, BC 5.50, and 8.6 mm diameter for her LE and combined with spectacle for her RE. Her over-refraction BCVA of the LE was 0.9. Discussion : The management goals are to improve the patient’s visual acuity and to decrease the progression. The visual acuity of this patient improved after RGP fitting. Conclusion : The combination of CXL procedure and the use of RGP effective to increase visual acuity, regularity of corneal surface, and patient satisfaction. Keratoconus should be monitored regularly to avoid possible progressivity.